Right ventricular function preservation in conduction system pacing (CSP): Impact of lead-to tricuspid annulus distance left bundle branch area pacing (LBBAP) vs. his-bundle pacing (HBP) - Mirza, Try Ahmad; Pranata, Raymond; Kamarullah, William; Iqbal, Mohammad; Hidayat, Syarief; Achmad, Chaerul; Karwiky, Giky (Heart Science Journal, 2026)
Background: Pacemaker remains the most effective therapy for the management of conduction disorders; however, traditional methods of right ventricular (RV) pacing have given way to more advanced conduction system pacing (CSP) techniques, such as His Bundle Pacing (HBP) and Left Bundle Branch Area Pacing (LBBAP). Objective: The impact of these two techniques on RV function is the objective of this study. Methods: This longitudinal prospective cohort study investigates differences in RV function among patients who have undergone HBP and those who have received LBBAP, using the echocardiographic parameters: fractional area change (FAC), RV global longitudinal strain (RVGLS), tricuspid annular plane systolic excursion (TAPSE), and the progression of tricuspid regurgitation (TR), with a focus on lead placement distance to the tricuspid annulus (TA) within LBBAP subgroup. Result: Among the 64 patients (33 in the HBP group and 31 in the LBBAP group), LBBAP patients with a lead-to-TA distance > 21.5 mm showed significantly better preservation of RV function across all metrics compared to HBP, specifically noted in TAPSE (1.83±5.34 vs. -1.06±3.77 in HBP, p=0.048), FAC (7.83±9.98 vs. 2.42±10.63 in HBP, p=0.011), and also RVGLS improvement (p=0.020). Conclusion: LBBAP with lead placement > 21.5 mm from the TA better preserves RV function compared to HBP mainly by minimizing mechanical interference with the tricuspid valve and reducing TR risk.